EFFECTIVENESS OF SUPERVISED TOOTH BRUSHING EXERCISE ON THE ORAL HYGIENE STATUS OF SCHOOL GOING CHILDREN IN PESHAWAR - Samrina Nasir; Rubab Jawed; Zeeshan Kibria; Shazia Makhdoom; Aiman Khan; Momina Saleem (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the effects of supervised tooth brushing exercise on the oral hygiene status of school going children in Peshawar.